Paper Swordsmen Jin Yong and the Modern Chinese Martial Arts Novel - Hamm, Christopher (University of Hawaii Press, 2004)
The martial arts novel is one of the most distinctive and widely-read forms of modern Chinese fiction. In Paper Swordsmen, John Christopher Hamm offers the first in-depth English-language study of this fascinating and influential genre, focusing on the work of its undisputed twentieth-century master, Jin Yong. Through close readings of Jin Yong’s recognized masterpieces, Hamm shows how these works combine a rich literary tradition with an extraordinary narrative artistry and an evolving appreciation of the political and cultural aspects of contemporary Chinese experience